Determinants of Online Food Delivery (OFD) towards Customer Behaviour: A Systematic Review - Ali Husin , Nursyuhada Ain binti (RSF Conference Series: Business, Management and Social Sciences, 2025)
Online food delivery (OFD) has become a trend worldwide. As it has emerged and revolved in the era of the gig economy, OFD is considered as a gig career where it has been popularized among urban cities and widely spread around the world. The demand of OFD has open opportunities for food aggregators in the industry to grasp whatever chances they had to open a medium to serve the consumers’ needs which is food. The packed daily schedule and convenience of the OFD system led to consumers’ motivation to utilize OFD as the answer to their hunger call. Therefore, scholars incorporate with the food aggregators in the industry were focusing on the customer behaviour and factors that triggered the consumers towards OFD over the recent years. Due to the many overlapping interests of studies, there is a gap in our understanding of consumers’ reasons for OFD usage. We addressed the gap by conducting an interdisciplinary systematic review of the relevant literature. Through critical evaluation and analysis of the literature, we identify major determinants that have been mostly considered by the consumers relating to the OFD usage: service quality, food quality, consumer experience and practicality. Finally, we propose few suggestions that can be useful as guidance for future research and create an insight for food aggregators to note.